USO SUSTENTÁVEL DE ESPÉCIES DE PALMEIRAS DA APA DA BAIXADA MARANHENSE PARA O CONTROLE E RECUPERAÇÃO DE ÁREAS DEGRADADAS POR EROSÃO - Mendonça, Jane Karina Silva (2006)
This study regards the sustainable development of the types of palms from Protection Environment Area (APA) in Baixada Maranhense, in the handcraft production of geotextile that has been used in the rehabilitation of some degraded areas by erosion and helps to involve the local poor community, as well as those people who work with handcraft and extraction activities of those plants. It has been carried out bibliography and cartography surveys, questionnaires that were filled, in order to assess the extraction and production of mats and tests of the effectiveness of the geotextile, through an experimental station. The species selected: babaçu, buriti, carnauba, and tucum, are appropriate to this new way of use, observing the limits that those plants and their environment demand, to have an activity that has the goal of the social economic environmental sustainability.